Microwave communication networks as a sustainable tool of rainfall monitoring for agriculture needs in Africa - David, N.; Gao, H. O.; Kumah, K. K.; Hoedjes, J. C. B.; Su, Z.; Liu, Yanyan (2019)
Commercial Microwave Links (CMLs), that provide the underlying framework for data transfer between cellular network base stations have been found effective for monitoring rainfall. Wireless infrastructure of this kind is deployed widely by communication providers across Africa and can be used as a complementary monitoring device to the sparse proprietary resources that exist currently, and at minimal cost, or as a substitute tool in the many cases where alternatives do not exist. Here we focus on the potential that lies in this novel approach to acquire valuable information required for agricultural needs over the poverty-stricken countries of Africa